Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - Amaral, N. B.; Rodrigues, T. S.; Giannini, M. C.; Lopes, M. I.; Bonjorno, L. P.; Menezes, P. I. S. O.; Dib, S. M.; Gigante, S. L. G.; Benatti, M. N.; Rezek, U. C.; Emrich-Filho, L. L.; Sousa, B. A.; et al. (Inflammation research, 2023)
Objective To evaluate whether colchicine treatment was associated with the inhibition of NLRP3 inflammasome activation in patients with COVID-19. Methods We present a post hoc analysis from a double-blinded placebo-controlled randomized clinical trial (RCT) on the effect of colchicine for the treatment of COVID-19. Serum levels of NOD-like receptor protein 3 (NLRP3) inflammasome products—active caspase-1 (Casp1p20), IL-1β, and IL-18—were assessed at enrollment and after 48–72 h of treatment in patients receiving standard-of-care (SOC) plus placebo vs. those receiving SOC plus colchicine. The colchicine regimen was 0.5 mg tid for 5 days, followed by 0.5 mg bid for another 5 days. Results Thirty-six patients received SOC plus colchicine, and thirty-six received SOC plus placebo. Colchicine reduced the need for supplemental oxygen and the length of hospitalization. On Days 2–3, colchicine lowered the serum levels of Casp1p20 and IL-18, but not IL-1β. Conclusion Treatment with colchicine inhibited the activation of the NLRP3 inflammasome, an event triggering the ‘cytokine storm’ in COVID-19. Trial registration numbers RBR-8jyhxh